Analisis pengaruh faktor kependudukan terhadap pertumbuhan ekonomi provinsi di Pulau Sumatera - Gustina, Maya; Yulmardi, Yulmardi; Hardiani, Hardiani (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2025)
This research aims to analyze: 1). economic growth, dependency ratio, labor force and human development index in provinces on Sumatra Island 2015-2022; 2). The influence of the dependency ratio, labor force and human development index on economic growth in provinces on the island of Sumatra 2015-2022. The method used in this research is a quantitative and descriptive method in the form of secondary data sourced from the Central Statistics Agency (BPS) from 2015-2022 with a Panel Data Regression analysis tool assisted by using the Eviews 9 software analysis tool. The results of this research using panel data regression analysis with the selected model Fixed Effect Model (FEM) show that the labor variable has a positive and significant effect on provincial economic growth on the island of Sumatra, the human development index (HDI) variable has a negative and significant effect on provincial economic growth in Sumatera island. Meanwhile, the dependency ratio variable does not have a significant effect on provincial economic growth on the island of Sumatra.